Understanding the behaviour of engineered nanoparticles in food - Ong, Pei Ying (2016)
It is well known that the cellular uptake and toxicity of nanoparticles can be altered by the presence of a corona formed on nanoparticles. Corona, a natural interface between nanoparticles and living matter in biological milieu, has garnered much attention lately as nanoparticles in food products may not exist as it is, due to the adsorption of food molecules. This alters the properties and biological identity, thus changing the fate of nanoparticles in the biological system. It is therefore the aim of this project to investigate the possible interactions of food ingredients, namely carbohydrates and proteins, with engineered nanoparticles. Food grade silicon dioxide (SiO2; E551), food grade titanium dioxide (TiO2; E171) and commercial silver (Ag) nanoparticles were suspended in sucrose and Bovine Serum Albumin (BSA) solutions of varying concentrations, and mixtures of food ingredients solution were also prepared to evaluate the affinity of each nanoparticle type to specific food ingredients. Thermal Gravimetric Analysis (TGA), micro BCA (bicinchoninic acid) protein assay and Fourier Transformed Infrared (FTIR) spectroscopy were used to measure the amount and identity of the corona. Results showed sucrose adsorption on SiO2 and TiO2, but not Ag nanoparticles, suggesting the negligible affinity of sucrose to Ag nanoparticles. For protein adsorption, SiO2 displayed the highest amount of adsorbed BSA, possibly owing to the small-sized particles which enabled greater exposed particle surface to interact with the surrounding molecules. For mixtures of food ingredient solutions, results revealed that the combination of low protein and high sucrose concentration demonstrated a synergistic effect of net total increase in the amount of sucrose-proteins molecules adsorbed to SiO2 nanoparticles. In addition, the effectiveness of sample washing for the isolation of hard corona complexes was also studied. It was revealed that two washes are sufficient to isolate the hard protein corona from the loosely bound proteins (soft protein corona). These findings are useful as they can be used as a basis for future approach to study and understand nanoparticle-corona complexes.